Air Pollutant of PM10 and PM2.5 on Air Quality Index in Business Center Kota Baru Parahyangan, West Bandung District - Wellid, Ismail; sugiyarto, sugiyarto; Simbolon, Luga Martin; Nur Fajrina, Gema Adzani; Nuryati, Neneng; bin Sukri, Mohamad Firdaus (Jurnal Internasional Penelitian Teknologi Terapan, 2024)
Kota Baru Parahyangan is located between Cimahi City and Padalarang. As an area designed as a satellite city, Kota Baru Parahyangan has various facilities including a business centre. In the present study, PM10 and PM2.5 will be measured at three business centres and one residential location located at the southernmost point for comparison. Data collection was carried out on 2 weekdays, namely Monday and Tuesday, and 2 weekends, namely Saturday and Sunday. The data collection time is from 08:00 to 15:30, where data collection is carried out every 30 minutes. Based on these measurements, PM10 and PM2.5 concentrations in three business centre locations and 1 residential location are still under the PPRI No. 22 of 2021 standards. Meanwhile, when evaluated using Kepmen LHK No. 14 of 2020, the API level for PM10 in three business centre locations and 1 residential location is in the "Good" category. However, the API level for PM2.5 in three business centre locations and 1 residential has reached the "Moderate" category. This means that the concentration of PM2.5 in business centre and residential in Kota Baru Parahyangan should be seriously considered by developer and local government. Because it is confirmed that PM2.5 concentrations will continue to increase over time with increasing activity and an increase in the number of vehicles passing through a region.